Design and implementation of aerial : aqua vehicle - Koh, Hui Xuan (2016)
Over the recent years, the unmanned aerial vehicle has gained much popularity and it has been widely used for various applications especially in the area of defence and security. Although the development of unmanned aerial vehicles has many potential advantages, there are still some existing drawbacks that are researched intensively. In Singapore, maritime surveillance is an area of concern due to the difficulty in patrolling in pervasive sea parameters and increasing frequency of pirate activities in that region. With the consideration of unmanned aerial vehicle’s drawbacks, this study aims to propose a design solution with the integration of a RC boat into the existing UAV design that can be used for this objective. With the understanding of its main components, different types of unmanned aerial vehicles and radio controlled boat are explored. In order to innovate various designs of the prototype, the use of systematic design methodology such as the functional analysis, morphological chart and weighted value analysis are investigated by the student to brainstorm, combine and evaluate. After finalising the concept sketch design, the student went on to build and install the prototype while conducting various experiment tests. As the unmanned aerial vehicle is smaller in size, the boat has to be built in proportional to its size and this has caused many challenges during the building process. These challenges includes the material selection, the effective packaging of the electronic parts as well as the radio transmission interface. Even though there are further improvements to be made in this study, this study had managed to set the foundation for future studies to build on and to explore the other possibilities of an aerial- aqua vehicle. With the various recommendation being listed in this study, they can help to consolidate the different possibilities of the prototype.